Assessment of RES technology market values and the merit-order effect – an econometric multi-country analysis. Issue 1 (February 2016) - Welisch, Marijke; Ortner, André; Resch, Gustav
This study presents an assessment of both the merit-order effect and the market values of electricity generated from variable renewable energy sources, namely wind and solar photovoltaics. The historical price development in several European countries – that cover 73% of the renewable energy source share in Europe's regional electricity markets – has been taken into account. To gain insights into the impact of renewable electricity on prices, market values and the merit-order effect were calculated using a multivariate regression analysis and ex-post calculations. All the countries analyzed show a consistent, negative impact of renewable electricity on electricity spot market prices and a decreasing market value of renewable energy source, possibly attributable to increased shares. The coefficients are economically and statistically significant. This study provides insights into a large geographical spread of European electricity markets, enables a comparison between countries, and therefore has valuable implications for policy makers.